2021
DOI: 10.2139/ssrn.3783818
|View full text |Cite
|
Sign up to set email alerts
|

Reforming the Individual Income Tax in Spain

Abstract: We study how much revenue can be generated by more progressive personal income taxes in Spain. We build a life-cycle economy with uninsurable labor productivity risk and endogenous labor supply. Individuals face progressive taxes on labor and capital incomes and proportional taxes that capture social security, corporate income, and consumption taxes. An increase (decrease) in labor income taxes for individuals who earn more (less) than the mean labor income generates a small additional revenue. The revenue fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…This discourages the labor supply of workers (−1.5%), accumulation of capital by entrepreneurs (−12.6%), and the overall output of the economy (−4.2%). These findings are consistent with those of Guner et al (2020) in a model without entrepreneurs. They find that τ = 0.19 maximizes revenue from personal income taxes, while total tax revenue decreases by 1.5%.…”
Section: Increasing the Degree Of Progressivity Of The Labor Income T...supporting
confidence: 90%
See 3 more Smart Citations
“…This discourages the labor supply of workers (−1.5%), accumulation of capital by entrepreneurs (−12.6%), and the overall output of the economy (−4.2%). These findings are consistent with those of Guner et al (2020) in a model without entrepreneurs. They find that τ = 0.19 maximizes revenue from personal income taxes, while total tax revenue decreases by 1.5%.…”
Section: Increasing the Degree Of Progressivity Of The Labor Income T...supporting
confidence: 90%
“…This utility function is consistent with balanced growth and with evidence from panel data that, conditional on education, mean lifetime hours of work do not vary across the distribution of lifetime wages (see Erosa et al 2016). The parameter γ is set so that the Frisch elasticity of labor supply equals 1/γ = 0.5 as in Guner et al (2020), which facilitates the comparability with their findings. The discount factor of time β and the weight of the disutility of work φ will be calibrated endogenously.…”
Section: Demographics and Preferencessupporting
confidence: 72%
See 2 more Smart Citations
“…Silvia Avram conducted a study on the redistribution effect of individual tax in several European countries through micro-simulation methods, and the results showed that the deduction of individual income tax is more obvious for middle-and upper-income groups [3]. Roberto Ramos, Nezih Guner and Javier López-Segovia found that the more progressive taxes, the lower the work income and quality of life of residents [4]. Li Jing and Niu Xuehong analyzed that the distribution effect of individual income tax income after the 2019 reform has weakened compared to before [5].…”
Section: The Relationship Between Individual Income Tax and Resident ...mentioning
confidence: 99%